Addressing the Covid-19 Pandemic: Chronicles from the Pastures - Farinella, Domenica; Simula, Giulia (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2020)
What logic and practices adopted by shepherds can we learn to deal with the uncertainty caused by the Coronavirus pandemic? For shepherds, uncertainty did not begin with Covid-19, it is part of everyday life. Severe droughts, floods, animal diseases, a sudden collapse in prices, a rise in the price of feed or diesel fuel. Pastoralism, a semi-extensive livestock farming system, is a production system forced to adapt every day to the variables of difficult ecosystems. Several examples of practices that have always been used as resilience mechanisms include strategies such as self-production, sales through local and regional networks, collaborative work, investments in a contingent future etc. But with the modernization and rationalization of the sector, these practices have been discouraged or even become illegal, increasing the costs for farms and disadvantaging above all small production in favour of a food system mainly focused on international exports. It is precisely small-scale production that paid the highest costs during the global pandemic that reached its peak in March 2020. In this article the authors retrace some chronicles of Sardinian shepherds during the Covid-19, underlining how they, already accustomed to living with uncertainty, have faced this new global challenge and highlighting what can be learned from shepherds, experts in managing uncertainty.